Efforts to Improve the Ability to Read the Qur'an Through the Iqra' Method at Deah Rungkom Elementary School - Hasanah (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to find out the efforts to improve the ability to read the Qur'an through the Iqra' method in Deah Rungkom Elementary School students, Aceh Besar Regency. The background of this research is the low ability to read the Qur'an among primary school students, which is caused by the lack of effective and sustainable learning methods. The Iqra' method was chosen because it is practical, systematic, and easy to understand by children of primary school age. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the research show that the application of the Iqra' method in a structured and intensive manner can significantly improve the ability to read the Qur'an. In addition, teacher involvement, parental support, and the availability of sufficient study time are supporting factors in the success of this method. In conclusion, the Iqra' method is effective in improving students' ability to read the Qur'an, especially if applied with a consistent and communicative approach.